Peningkatan Kemampuan Mahasiswa dan Pendampingan dalam Pembuatan Nomer Induk Berusaha (NIB) dan Sertifikat Halal Produk UMKM - Zahrah, Zahrah; Makiah, Makiah; Widiyasti, Baiq Dinna; Patty, Elyakim Nova Supriyedi (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
Collaboration between the business world and academic institutions serves as the cornerstone for fostering economic growth. However, in practice, the management of legality remains a challenge for MSMEs and students, who lack a clear understanding of how to manage it. Consequently, the importance of community service, particularly in the management of NIB and Halal Certificates, cannot be overstated. This community service activity was designed for students and 26 MSMEs in Mataram City and West Lombok Regency, employing a community service approach that was structured into two sessions: the first session is the provision of materials, while the second session focused on counseling and direct mentoring. This initiative spanned one year (from May 2024 to May 2025) in accordance with the stipulated free halal certificate quota allocated by the government program. The outcomes of this community service initiative encompassed students' mastery of the advantages of business legality and the process of acquiring NIB and Halal Certificates, students assisted business owners in obtaining these two legal documents, and facilitated the acquisition of NIB and Halal certificates for business owners more easily and effectively through the collaborative of community service team and students who had undergone training by the community service team.